The nutrition and health risks faced by pregnant adolescents: Insights from a cross-sectional study in Bangladesh - Nguyen, Phuong Hong; Sanghvi, Tina; Tran, Lan Mai; Afsana, Kaosar; Mahmud, Zeba; Menon, Purnima; Massimo Ciccozzi (Public Library of Science, 2017)
Little is known about nutrition and well-being indicators of pregnant adolescents and the availability and use of nutrition interventions delivered through maternal, newborn, and child health (MNCH) programs. This study compared the differences between pregnant adolescents and adult pregnant women in services received, and in maternal and child nutrition and health conditions. A survey of 2,000 recently delivered women with infants <6 months of age was carried out in 20 sub-districts in Bangladesh where MNCH program is being implemented. Differences in service use and outcomes between pregnant adolescents and adult women were tested using multivariate regression models.